Development of a Long-Range WAN Weather and Soil Monitoring System for Rural Farmers - Njoku, Uchechi C.; Agubor, Cosmas K.; Ezema, Longinus S. (Eximia, 2022)
Increasing security concerns in areas where insurgency persist, calls for reduced visitation of the farmers to their farms, consequently affecting produce. This calls for remote monitoring of the environmental weather and soil conditions of the farmland in order to trigger irrigation automatically. Traditional broadband systems used for remote monitoring of soil and environmental weather conditions require high cost and focuses on enabling high data rates per device and are not energy efficient. In this work, Long Range Wireless Area Network (LoRaWAN) has been presented, a new trend in the evolution of the wireless communication technologies to provide energy efficient system that requires no data cost for monitoring. In achieving this, BME280-Temperature, Humidity and Pressure Sensors, ESP32 LoRa transmitter and receiver modules were used. Arduino C++ programming language was used for the ESP32 controller. A wireless access point was established between the transmitter and receiver; and sensor-data was transmitted seamlessly from the transmitter to the receiver, updating every 10seconds. The result at the receiver visualized on the Organic Light Emitting Diodes (OLED) or via mobile phone at no data cost shows the Received Signal Strength Indicator (RSSI), Temperature, Pressure and Humidity values at real time. Automatic DC Sprinkler system triggered when the BME280 sensor threshold values for pressure and temperature were met.